RETOLD: CIDOC CRM and the Documentation of Buildings and Crafts - Cordula Hansen (EXARC Journal)
Cultural heritage documentation is the process of systematically recording and preserving information about historical artifacts, monuments, traditions, and other intangible cultural expressions. One of the primary aims of the RETOLD project was to create a prototype for immersive digital storytelling that communicates cultural information to diverse audiences, museum professionals and museum workers in an understandable and engaging way. We aimed to co-design with the museum partners a piece of technology that would address the most pressing aspects of digital storytelling relevant to open-air museums.